Effects of Co on microstructure evolution of a 4th generation nickel-based single crystal superalloys. (February 2023) - Pan, Qinghai; Zhao, Xinbao; Cheng, Yuan; Yue, Quanzhao; Gu, Yuefeng; Bei, Hongbin; Zhang, Ze
Abstract: For further composition optimization, the microstructure evolution of the fourth-generation nickel-based single crystal superalloys, which contains different Co (Cobalt) additions, is studied at three thermal exposure temperatures. Based on Lifshitz, Slyozov and Wagnerz (LSW) theory and trans-interface diffusion-controlled (TIDC) theory, the effects of Co content and aging temperatures on coarsening rate of γ′ phase are investigated in detail. The results show that the diffusion coefficient of solute is accelerated, but the γ/γ′ interfacial energy decreases with the addition of Co, thus changing the coarsening rate. Furthermore, the thermodynamic equilibrium solubility difference of elements between γ′ and γ, and the segregation of elements at the γ/γ′ interface are alleviated with increase of Co, resulting in the suppression of TCP phase after long-time thermal exposure, which guides the economical design of nickel-based single crystal superalloys. Highlights: Co additions have a dual effects on microstructure evolution of the superalloys. The effect of Co on coarsening rate of γ′ depends on temperature. The accuracy of two coarsening prediction models is tested.